A History of Modern Jewish Religious Philosophy : Volume IV: The Crisis of Humanism (II). The End of the Jewish Center in Germany - Schweid, Eliezer, (Supplements to The Journal of Jewish Thought and Philosophy ;, 2023)
The last generation of German Jewish philosophers brought the long, tragic history of German-Jewish creative thought to a close in a blaze of glory, while transitioning to the new Jewish creative centers in Israel and America. The best known (Buber, Rosenzweig, Baeck, Strauss, Scholem) and the less known (Breuer, Birnbaum, Klatzkin, Aviad-Wolfsberg, Guttmann) are thoroughly explicated here, with generous primary text citations appearing in English for the first time, making this a rich sourcebook and reference for the thinkers presented.